If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t(9 + t) = 2(2t + 7) (9 * t + t * t) = 2(2t + 7) (9t + t2) = 2(2t + 7) Reorder the terms: 9t + t2 = 2(7 + 2t) 9t + t2 = (7 * 2 + 2t * 2) 9t + t2 = (14 + 4t) Solving 9t + t2 = 14 + 4t Solving for variable 't'. Reorder the terms: -14 + 9t + -4t + t2 = 14 + 4t + -14 + -4t Combine like terms: 9t + -4t = 5t -14 + 5t + t2 = 14 + 4t + -14 + -4t Reorder the terms: -14 + 5t + t2 = 14 + -14 + 4t + -4t Combine like terms: 14 + -14 = 0 -14 + 5t + t2 = 0 + 4t + -4t -14 + 5t + t2 = 4t + -4t Combine like terms: 4t + -4t = 0 -14 + 5t + t2 = 0 Factor a trinomial. (-7 + -1t)(2 + -1t) = 0Subproblem 1
Set the factor '(-7 + -1t)' equal to zero and attempt to solve: Simplifying -7 + -1t = 0 Solving -7 + -1t = 0 Move all terms containing t to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1t = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1t = 0 + 7 -1t = 0 + 7 Combine like terms: 0 + 7 = 7 -1t = 7 Divide each side by '-1'. t = -7 Simplifying t = -7Subproblem 2
Set the factor '(2 + -1t)' equal to zero and attempt to solve: Simplifying 2 + -1t = 0 Solving 2 + -1t = 0 Move all terms containing t to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1t = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1t = 0 + -2 -1t = 0 + -2 Combine like terms: 0 + -2 = -2 -1t = -2 Divide each side by '-1'. t = 2 Simplifying t = 2Solution
t = {-7, 2}
| 5x+5=-6+3x+25 | | Y=cos^2(3x) | | 3sqrt(x+2)=8 | | [x+4][x+4]=1 | | [x+4]2=1 | | 9t+5=6t-10 | | 19-7-13X=3(2X-3)+2 | | 50=-x-23 | | [x+4][x-5]=10 | | t^2=14t-49 | | [2x-9][x+3]=0 | | X-9(X+5)-7=11+3(9-3X)-81 | | 144-(6X+11)=6(X+7)+X | | 7+8a+a^2=0 | | 10x+2y=44 | | 6(p+1)(p+2)=0 | | 13x^2-3x^2=20x+13x | | 5xsquared=100 | | c=ab+d | | X^2-6x+y^2+10y=66 | | 8g+4-5=-5 | | 0=6n^2-43n | | 18x^3-5720=0 | | 4x^2=448 | | x^2-8x-9200=0 | | 4x-3=3(x+1) | | (3a+2)-11b=0 | | 4+3x+1=2x+5+x | | 4x-5=4x+3 | | 3t^2-8t-20=0 | | 23730=x+.13x | | 3x-12x^2=0 |